Implementasi Program Pemberian Makanan Tambahan (PMT) Lokal Bagi Balita di Kelurahan Nunbaun Delha, Kecamatan Alak, Kota Kupang - Langaih, Nova Elisabeth; Kase, Petrus; Oktavianto, Aspri Budi; Djani, William (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine how the implementation of the local food-based supplementary feeding program for toddlers in Nunbaun Delha Village, Alak District, Kupang City. This study uses a qualitative descriptive approach using four indicators of policy implementation, namely communication, resources, disposition, and bureaucratic structure. The results showed that the implementation of the program was confusing for implementers because it was initially informed that it would begin in May 2023, but it was only realized in September-November 2023, and was not continued in 2024 in Kelurahan Nunbaun Delha. Incentives for posyandu cadres are channeled weekly through bank accounts, but are considered inefficient because small amounts have to be collected directly at the bank. PMT cooking facilities are provided by the cadres themselves with their own funds due to budget constraints. In addition, some toddlers refuse food because it does not match their taste and texture preferences, so food is often consumed by other family members. In conclusion, although there are still some obstacles, this program has been implemented in accordance with the provisions so that it can improve the nutritional status of the target.